Assessment the Effects of Heavy Elements on Some Hematological Parameter in CKD Patients Undergoing Hemodialysis in Thi-Qar Province / Iraq . - Al-khafaji, Noora; Bassim Y. Al-khafaji; Dheyaa K. Al-Omar (University of Thi-Qar Journal of Science, 2024)
The present study aimed to assess the level of heavy elements (HEs) (Pb, Cd, Cu and Zn) in blood serum and their effects upon selected parameters (WBC, RBC, Hb and PLT.) in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) in Thi-Qar province Iraq. The study was from Sept 2022 until July 2023. Fifty samples of blood were taken from patients with CKD, whereas 25 samples were takenfrom healthy people (males and females as a control group. The patients and the controlroup ranged from (17-76) years. All the patients were submitted to the HD for (1-15) yeas in Al-Hussain Hospital in the mentioned province. The results showed that the sex ratio of the samples was more than 70% for males and 30% females respectively, and the high number of the patients with CKD was 48% for the advance age group (57-76). The mean concentration of (Cd, Cu, Zn and Pb) in the blood serum of patients pre HD were 0.065±0.018, 0.014±0.006, 0.016±0.008 and 1.041±0.38 mg/L respectively, Pb and Cd recorded the higher mean concentration, while Cu and Zn recorded lower concentration compared to the control group .The mean count of (WBC, RBC, Hb and PLT) were decreased , recorded 2.78±0.79, 3.06±0-54, 8.54±1.43 and 164.4±51.8 respectively , it concluded from the present study that the CKD affected the hematological parameters directly while HEs affected indirectly.